Peningkatan Kemampuan Menulis Teks Persuasi dengan Menggunakan Teknik Pemodelan Siswa Kelas VIII SMPN L Sidoharjo Kabupaten Musi Rawas - Arida, Elpi; Susetyo, Susetyo; Yulistio, Didi (UNIB Press, 2020)
The purpose of this study was to describe (1) increasing the ability to write persuasion text with the modeling techniques of eighth grade students of SMPN L. Sidoharjo, Musi Rawas Regency and (2) Increasing student learning activities in writing persuasive text with modeling techniques for VIII students of SMPN L. Sidoharjo, Musi Regency Rawas. This study uses a Classroom Action Research (CAR) procedures. This research was conducted in two cycles. Each cycle is designed and carried out by steps (1) planning, (2) action, (3) observation, and (4) reflection. The source of the data of this study was the eighth grade students of SMP N L. Sidoharjo in the 2018/2019 academic year, while the research data were in the form of persuasion texts written by students. Then the data is analyzed using the average formula and the results are consulted in the qualification table. The results showed that the ability to write persuasion texts students experienced an average increase in cycle 1 of 67.98 which included in the category of enough, increased to 77, 76 in the second cycle included in the good category. The increase was also followed by an increase in student activity in learning to write persuasion texts which included activeness and direct involvement in observing, answering questions and writing persuasion texts from moderately active to active.